Examining The Mechanism of Influencers to Motivate Urge of Impulsive Buying Through Tik Tok - Mahendra Wahyu Isyaka Putra; Erlita Ridanasti (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
The rapid growth of social commerce has intensified the role of social media influencers in shaping consumer purchasing behavior, particularly impulsive buying on platforms such as TikTok. This study examines the mechanism through which influencer credibility, message credibility, and media credibility influence consumers’ urge to buy impulsively, with trust in branded posts serving as a mediating variable. Grounded in the Stimulus–Organism–Response (SOR) framework, this research employs a quantitative approach using survey data collected from 150 Indonesian TikTok users who have purchased products promoted by a social media influencer. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. Results in this research indicate a positive effect of trust in branded posts on Urge to Buy Impulsively. The findings additionally indicate that the trust in branded posts is heavily influenced by Influencer Credibility, Message Credibility, and Media Credibility.